(3GdESYGa GdCJe HCMGSf Gdafhf hMSGH Gdbdes - (3YKeGf Hf YdGAGdOjf Hf jhfS Hf eMeO GdTgjQ HGHf Gdedc GdOeTbjs; (3CHh GdMSf Ydj Hf eMeO Hf Ydj GdWHQj, GdcjGgQGSj,J (B504 (3g` s ((3Ydi Hf SGde GdOeGWi GdeGdci s)
(3ChdgG (B:s
(3Ef CSfi eG SeYJ Hg GdNhGWQ , hCSei eG Qbe ai GdCacGQ hGdOaGJQ MeO GdChd GdaQO GdMSjH s
(3Cdag SfI (B1002 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B329s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B357 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B11 s
Keywords: (3GdQjGVjGJs